HOST STATE CONTROLS VS. FOREIGN INVESTMENT PROTECTION: INDIGENOUS PEOPLE RIGHTS ON REMPANG ISLAND, INDONESIA - Halim, Abdul (Kanun Jurnal Ilmu Hukum, 2024)
The enactment of national Law No. 25 of 2007 on Investment is carried out in the framework of uplift the initiation of a favorable domestic business condition for investment to reinforce the competitiveness of the domestic economy and advance investment; while the right of indigenous has been marginalized. The recent case of conflict between the government investment policy and the Indeginous people under the Rempang Eco City project in Batam is remain contentious. This article utilized the normative approaches to investigate this issue, and Rempang case become a context to investigate. Resolving land tenure conflicts between the local community and BP Batam must begin with tracing the history of the land through history, cultural heritage, natural physical signs, recognition and testimony from residents and traditional institutions. Protecting foreign investors must also take care of indeginous people rights surrounding it.